Analysis Of Timeliness Return of Outpatient Medical Record Daily Document at Pandanwangi Community Health Centre (Puskesmas), Malang, Indonesia: Ali Hanafiah*, Femy Anggriyani, Ach. Choirul Anwar, Andhika Putra Eka Wijaya - Ali Hanafiah; Femy Anggriyani; Ach. Choirul (JOURNAL OF MEDICAL RECORDS AND HEALTH INFORMATION, 2020)
Medical Record is a written proof of the process of service provided to patients by doctors and medicalpersonnel, while with the existence of such written evidence the medical record can be justified therefore theaccuracy of the return of medical record files is very important for service and for data processing. Toconsistently improve doctors and medical personnel such as nurses in returning outpatient medical record filesto medical record units, good collaboration and high discipline of health workers is required. The purpose of thisstudy is to know in general the description and timeliness of daily document recording of outpatient medicalrecords to the unit of Medical Record at Puskesmas Pandanwangi and to identify the problem of non-timelinessof return of daily medical record document to the Medical Record Unit. The result of this research is a researchusing descriptive analysis method with qualitative approach. Data collection techniques used by researchers areobservation and interview. Methods Data analysis used is descriptive method that aims to create a description ofa situation objectively. The result of the research proves that in general the reason for the delay of return ofmedical record file is the lack of discipline factor from health officer like doctor or nurse. As a result ofthorough research, documents are returned on time (1x24 hours) 1846 documents and documents that are late(more than 1x24 hours) 136 documents. From the calculation it can be seen that the number of medical recorddocuments that return on time is greater than the late medical record and for the percentage of return of medicalrecord documents in July 2017 is for the Medical Record of Outpatient that is returned on time is 1x24 hours of93, 14% and for outpatient medical records returned over the specified time of 1x24 hours at 6.86%.Keyword : Timeliness, Daily Medical Record Document, Outpatient